Membrane and electrode
By using a combination of polymers with anionic and cationic functional groups and MXene particles to form high-strength and low-impedance films, the problem of insufficient strength of existing MXene composite materials is solved and is suitable for high-performance electrode applications.
Patent Information
- Application Number
- CN202380038615.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-18
- Filing Date
- 2023-03-06
- Publication Date
- 2024-12-13
AI Technical Summary
The existing MXene composite foam has low strength and no impedance mentioned, making it difficult to meet the high-strength and low-impedance electrode requirements.
A film containing two-dimensional material particles of one or more layers and a polymer having anionic and cationic functional groups is used to form a high-strength and low-impedance film by preparing and drying the liquid composition for electrodes.
High-strength and low-impedance films are achieved, suitable for electrodes, especially in the fields of biological signal sensing and electromagnetic shielding.
Smart Images

Figure CN119137685A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a membrane and an electrode using the membrane. Background Art
[0002] In recent years, MXene has attracted much attention as a new type of conductive material. MXene is a so-called two-dimensional material. More specifically, as described later, it is a two-dimensional material (layered material) having one or more layers. Generally speaking, MXene has the form of particles (which may include powder, flakes, nanosheets, etc.) of such a two-dimensional material (layered material).
[0003] In the past, composite materials of MXene and polymers are known. For example, Patent Document 1 describes that a mixed solution containing MXene and polyisocyanate is reacted with a mixed solution containing other materials (other MXene, graphene, carbon nanotubes, oxide particles, etc.) and polyether in a mold by applying the principle of polyurethane foaming to obtain a MXene composite foam in which MXene and the other materials are compounded in a foamed polyurethane.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Chinese Patent Application Publication No. 112300363 Summary of the invention
[0007] Problems to be solved by the invention
[0008] A film containing MXene and a polymer can exhibit conductivity, and the use of the conductive film as an electrode has been studied. Electrodes, such as biosignal sensing electrodes, are required to have sufficient strength and as low impedance as possible. However, the MXene composite foam described in Patent Document 1 has the disadvantage of low strength. In addition, Patent Document 1 does not mention the impedance of the MXene composite foam.
[0009] An object of the present invention is to provide a novel film comprising MXene and a polymer and having high strength and low impedance. Another object of the present invention is to provide an electrode using the film.
[0010] Means for solving problems
[0011] According to one aspect of the present invention, a film is provided, the film comprising particles of a two-dimensional material and a polymer, the particles of the two-dimensional material comprising one or more layers,
[0012] The above layers include:
[0013] By the following formula: M m Xn represents the layer body and the modification or terminal T present on the surface of the layer body,
[0014] (wherein, M is at least one metal of Group 3, 4, 5, 6, or 7,
[0015] X is a carbon atom, a nitrogen atom or a combination thereof,
[0016] n is greater than or equal to 1 and less than or equal to 4,
[0017] m is greater than n and less than 5),
[0018] (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom),
[0019] The polymer has anionic functional groups and cationic functional groups.
[0020] The ratio of the polymer in the film to the total of the particles of the two-dimensional material and the polymer is 5 volume % or more and 70 volume % or less.
[0021] According to another aspect of the present invention, there is provided an electrode comprising the above-mentioned film.
[0022] Effects of the Invention
[0023] According to the present invention, a novel film containing a polymer and particles of a predetermined two-dimensional material (also referred to as "MXene" in this specification) and having high strength and low impedance can be provided. In addition, according to the present invention, an electrode using the film can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic cross-sectional view showing a film in one embodiment of the present invention.
[0025] Figure 2 is a schematic cross-sectional view showing a particle of a two-dimensional material (MXene) that can be used in one embodiment of the present invention. Figure 2 (a) represents a single-layer MXene particle. Figure 2 (b) shows multi-layer (two-layer in the example) MXene particles. DETAILED DESCRIPTION
[0026] Hereinafter, a film (more specifically, a conductive film) in one embodiment of the present invention will be described in detail, but the present invention is not limited to this embodiment.
[0027] Reference Figure 1The film 20 of this embodiment includes particles 10 of a predetermined two-dimensional material (layered material), and a polymer having anionic functional groups and cationic functional groups (hereinafter, also referred to as "amphoteric polymer" in the present invention) 11, and the ratio of the amphoteric polymer 11 in the film 20 to the total of the particles 10 of the predetermined two-dimensional material and the amphoteric polymer 11 is 5 volume % or more and 70 volume % or less. By using the amphoteric polymer 11 in combination with the particles 10 of the predetermined two-dimensional material (layered material), a film 20 with high strength and low impedance can be realized.
[0028] Hereinafter, the film 20 of the present embodiment will be described in detail by way of its production method. Unless otherwise specified, the description of the film production method can also be applied to the film itself.
[0029] The method for manufacturing the film of this embodiment includes:
[0030] (a) preparing a liquid composition comprising particles of a predetermined two-dimensional material (layered material), a polymer having anionic and cationic functional groups, and a liquid medium; and
[0031] (b) A step of forming a precursor film on a substrate using the liquid composition and at least drying the precursor film to obtain a film.
[0032] Process (a)
[0033] <MXene particles>
[0034] First, particles of a predetermined two-dimensional material (layered material) are prepared. The predetermined two-dimensional material that can be used in this embodiment is MXene, which is defined as follows:
[0035] The two-dimensional material (which can be understood as a layered compound, also represented as "M m X n T s ”, s is an arbitrary number. In the past, x was sometimes used instead of s) is a two-dimensional material (layered material) containing one or more layers.
[0036] This layer includes:
[0037] By the following formula: M m X n (wherein, M is at least one metal of Group 3, 4, 5, 6, or 7, and may include so-called early transition metals, such as at least one selected from Sc, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, and Mn; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 to 4; and m is greater than n and 5 to 5) (the layer body may have a lattice in which each X is located within an octahedral array of M); and
[0038] A modified or terminal T (T is at least one selected from a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom) present on the surface of the layer body (more specifically, at least one of the two surfaces of the layer body facing each other).
[0039] Typically, n may be 1, 2, 3 or 4, but is not limited thereto.
[0040] In the above formula of MXene, M is preferably at least one selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo and Mn, and more preferably at least one selected from Ti, V, Cr and Mo.
[0041] The above formula of known MXene: M m X n Expressed as follows.
[0042] Sc2C, Ti2C, Ti2N, Zr2C, Zr2N, Hf2C, Hf2N, V2C, V2N, Nb2C, Ta2C, Cr2C, Cr2N, Mo2C, Mo 1.3 C.Cr 1.3 C, (Ti, V) 2C, (Ti, Nb) 2C, W2C, W 1.3 C, Mo2N, Nb 1.3 C.Mo 1.3 Y 0.6 C (In the above formula, "1.3" and "0.6" mean approximately 1.3 (= 4 / 3) and approximately 0.6 (= 2 / 3), respectively.)
[0043] Ti3C2, Ti3N2, Ti3(CN), Zr3C2, (Ti, V)3C2, (Ti2Nb)C2, (Ti2Ta)C2, (Ti2Mn)C2, Hf3C2, (Hf2V)C2, (Hf2Mn)C2, (V2Ti)C2, (Cr2Ti)C2, (Cr2V)C 2. (Cr2Nb)C2, (Cr2Ta)C2, (Mo2Sc)C2, (Mo2Ti)C2, (Mo2Zr)C2, (Mo2Hf)C2, (Mo2V)C2, (Mo2Nb)C2, (Mo2Ta)C2, (W2Ti)C2, (W2Zr)C2, (W2Hf)C2,
[0044] Ti4N3, V4C3, Nb4C3, Ta4C3, (Ti, Nb)4C3, (Nb, Zr)4C3, (Ti2Nb2)C3, (Ti2Ta2)C3, (V2Ti2)C3, (V2Nb2)C3, (V2Ta2)C3, (Nb2Ta2)C3, (Cr2Ti2)C3, (Cr2V 2)C3, (Cr2Nb2)C3, (Cr2Ta2)C3, (Mo2Ti2)C3, (Mo2Zr2)C3, (Mo2Hf2)C3, (Mo2V2)C3, (Mo2Nb2)C3, (Mo2Ta2)C3, (W2Ti2)C3, (W2Zr2)C3, (W2Hf2)C3, (Mo 2.7 V 1.3 )C3 (In the above formula, "2.7" and "1.3" mean approximately 2.7 (=8 / 3) and approximately 1.3 (=4 / 3), respectively.)
[0045] Typically, M m X n The invention is selected from Ti2C, Ti3C2, Ti3(CN), (Cr2Ti)C2, (Mo2Ti)C2, (Mo2Ti2)C3 and (Mo 2.7 V 1.3 )At least one of C3 is represented.
[0046] In particular, M m X n It can be Ti3C2.
[0047] The MXene particles (hereinafter, simply referred to as “MXene particles”) can be synthesized by selectively etching (removing and, if necessary, performing layer separation) A atoms (and, if necessary, part of M atoms) from a MAX phase as a raw material.
[0048] In other words, the film manufacturing method of the present embodiment may further include a step of obtaining MXene particles before step (a), and the step of obtaining MXene particles includes a step of etching the MAX phase as a raw material with an etching solution (etching treatment).
[0049] The MAX phase as a raw material (hereinafter, also referred to as "MAX raw material") is represented by the following formula: m AX n express,
[0050] (In the formula, M, X, n, and m are as described above, A is at least one element of Group 12, 13, 14, 15, or 16, usually an element of Group A, typically Group IIIA and Group IVA. More specifically, it may include at least one selected from Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, S, and Cd, preferably Al).
[0051] The MAX phase has a crystal structure in which a layer composed of A atoms is located between two layers shown by M m X n (The lattice may have each X located within the octahedral array of M). The MAX phase typically has the following repeating unit when m = n + 1, that is, a layer of X atoms is disposed between each of the layers of the (n + 1) layers of M atoms (collectively also referred to as "M m X n layer"), and a layer of A atoms ("A atom layer") is disposed as the next layer to the (n + 1)th layer of M atoms, but is not limited thereto. By selectively etching (removing and, if necessary, layer-separating) A atoms (and, if necessary, a part of M atoms) from the MAX phase, the A atom layer (and, if necessary, a part of M atoms) is removed, and hydroxyl groups, fluorine atoms, chlorine atoms, oxygen atoms, hydrogen atoms, etc. present in the etching solution (usually an aqueous solution containing hydrofluoric acid, but not limited thereto) are modified on the surface of the exposed M m X n layer, and such a surface is used as the end.
[0052] The etching solution may contain any suitable acid (HF, HCl, HBr, HI, sulfuric acid, phosphoric acid, nitric acid, etc.).
[0053] For example, the MAX raw material can be etched with an etching solution containing hydrofluoric acid. By using hydrofluoric acid (Japanese: フッ酸) in the etching solution, hydrofluoric acid (HF) (Japanese: 7ツ化水素酸) is present in the etching solution. The etching treatment using an etching solution containing hydrofluoric acid may also be referred to as the ACID method. In addition to hydrofluoric acid, the etching solution may further contain other acids, such as hydrochloric acid, hydrobromic acid, hydroiodic acid, nitric acid, sulfuric acid, acetic acid, formic acid, hypochlorous acid, fluorosulfonic acid, etc.
[0054] Alternatively, for example, the MAX raw material can be etched with an etching solution containing a fluoride and an acid (wherein, hydrofluoric acid is not included). By using a fluoride and an acid (wherein, hydrofluoric acid is not included) in the etching solution, hydrofluoric acid (HF) is present in situ (Japanese: イン·サイチユ) in the etching solution. The etching process performed using an etching solution containing a fluoride and an acid (wherein, hydrofluoric acid is not included) can also be referred to as a MILD method. As a fluoride, a metal fluoride such as lithium fluoride, sodium fluoride, potassium fluoride, etc. can be used, and in particular, lithium fluoride can be used. In the case of using a metal fluoride, in the etching process, a metal (metal ion) can be intercalated into the MXene particles together with the etching of the MAX raw material. As an acid (wherein, hydrofluoric acid is not included), for example, hydrochloric acid, hydrobromic acid, hydroiodic acid, nitric acid, sulfuric acid, acetic acid, formic acid, hypochlorous acid, fluorosulfonic acid, etc. can be used, and in particular, hydrochloric acid can be used. As a fluoride and an acid (wherein, hydrofluoric acid is not included), ammonium difluoride can be used.
[0055] The process of obtaining MXene particles may appropriately include any suitable treatment after the etching treatment. As the treatment, for example, cleaning, intercalation, delamination, etc. can be cited. Cleaning can be based on any suitable cleaning medium, such as water, dilute hydrochloric acid, etc., and then centrifugation / decantation can be performed. Intercalation can insert metals (metal ions) into MXene particles. Delamination can be to promote the layer peeling of MXene particles by applying shocks such as vibration and / or ultrasound (making multilayer MXene particles into MXene particles with fewer layers, such as single-layer MXene particles). For example, delamination treatment for a specified time can be performed by hand shaking (Japanese: ハンドシエイク), automatic shaking table, mechanical oscillator, vortex mixer, homogenizer, ultrasonic bath, etc.
[0056] It should be noted that in the present invention, the MXene particles may contain a relatively small amount of residual A atoms, for example, 10% by mass or less relative to the original A atoms. The residual amount of A atoms may preferably be 8% by mass or less, more preferably 6% by mass or less. However, even if the residual amount of A atoms exceeds 10% by mass, there is sometimes no problem depending on the purpose and use conditions of the film.
[0057] MXene particles synthesized in this way10 Figure 2 As shown schematically, it can be a particle of a layered material including one or more MXene layers 7a, 7b (as an example of MXene particles 10, in Figure 2 (a) shows a single layer of MXene particles 10a. Figure 2 In (b), two layers of MXene particles 10b are shown, but the invention is not limited to these examples). In more detail, the MXene layers 7a and 7b have MXene particles 10a and 10b. m X n The layer body (Mm X n MXene layers 7a and 7b are also represented by “MXene layers”. m X n T s ”, s is an arbitrary number. The MXene particle 10 may be a particle in which each MXene layer is separated and exists as one layer ( Figure 2 The single-layer structure shown in (a), the so-called single-layer MXene particle 10a), may also be a stacked body in which a plurality of MXene layers are stacked separately from each other ( Figure 2 The multilayer structure shown in (b), so-called multilayer MXene particles 10b), can also be a mixture thereof. The MXene particles 10 can also be particles (also referred to as powder or flakes) that are aggregates composed of single-layer MXene particles 10a and / or multilayer MXene particles 10b. In the case of multilayer MXene particles, two adjacent MXene layers (e.g., 7a and 7b) are not necessarily completely separated, but may be partially in contact.
[0058] Although not limited to the present embodiment, the thickness of each layer of MXene (equivalent to the above-mentioned MXene layers 7a and 7b) is, for example, greater than 0.8 nm and less than 5 nm, especially greater than 0.8 nm and less than 3 nm (may vary mainly according to the number of M atomic layers contained in each layer), and the maximum size in the plane parallel to the layer (two-dimensional sheet plane) (which can correspond to the "in-plane size" of the particle) is, for example, greater than 0.1 μm, especially greater than 1 μm, for example less than 200 μm, especially less than 40 μm.
[0059] In the case where the MXene particles are laminated (multilayered MXene) particles, the interlayer distance (or void size, in Figure 2 Δd in (b) is not particularly limited, and is, for example, 0.8 nm or more and less than 10 nm (i.e., 8 A or more and less ), in particular not less than 0.8 nm and not more than 5 nm, more particularly about 1 nm, and the maximum dimension in a plane perpendicular to the stacking direction (two-dimensional sheet plane) (which can correspond to the "in-plane dimension" of the particle) is, for example, not less than 0.1 μm, in particular not less than 1 μm, for example not more than 100 μm, in particular not more than 20 μm.
[0060] The total number of layers in the MXene particles can be 1 or more than 2, for example, 1 or more and 20 or less, and the thickness in the stacking direction (which can correspond to the "thickness" of the particles) is, for example, 0.8 nm or more and 20 nm or less.
[0061] In the case where the MXene particles are laminated (multilayer MXene) particles, they may be MXene with a small number of layers. The term "small number of layers" means, for example, that the number of layers of the MXene is less than 6. In addition, the thickness of the multilayer MXene with a small number of layers in the stacking direction may be less than 10 nm. In this specification, the "multilayer MXene with a small number of layers" is also referred to as "few-layer MXene".
[0062] Although not limited to the present embodiment, most of the MXene particles may be particles (also referred to as nanosheets) composed of single-layer MXene and / or few-layer MXene. In this specification, single-layer MXene and few-layer MXene are sometimes collectively referred to as "single-layer·few-layer MXene".
[0063] It should be noted that the above-mentioned dimensions can be obtained as the number average size (for example, the number average of at least 40) based on scanning electron microscope (SEM), transmission electron microscope (TEM) or atomic force microscope (AFM) photographs, or the distance in actual space calculated from the position on the reciprocal lattice space (Japanese: inverse lattice space) of the (002) plane measured by the X-ray diffraction (XRD) method.
[0064] <Amphoteric Polymer>
[0065] In addition, an amphoteric polymer is prepared. In the present invention, an "amphoteric polymer" is a polymer having an anionic functional group and a cationic functional group. The polymer may be composed of one or more monomer units. A monomer unit refers to a structural unit derived from a monomer as a raw material of the polymer. Anionic functional groups and cationic functional groups may exist in the same monomer unit or in separate monomer units.
[0066] Anionic functional groups refer to parts that show anionicity (negative charge) in liquid media. Anionic functional groups can be, for example, at least one selected from carboxylic acid groups, carboxylate groups, sulfonic acid groups, sulfonate groups, phosphoric acid groups and phosphate groups (which can be any part of them). Anionic functional groups can exist in one or more types in the amphoteric polymer.
[0067] Cationic functional groups refer to parts that show cationicity (positive charge) in liquid media. For example, the cationic functional group can be at least one selected from amines, phosphines and their salts (can be any part of them), and more specifically, can be at least one selected from primary amines, secondary amines, tertiary amines, their acid salts and quaternary ammonium salts, and primary phosphines, secondary phosphines, tertiary phosphines, their acid salts and quaternary phosphonium salts. There can be one or more cationic functional groups in the amphoteric polymer.
[0068] For example, the amphoteric polymer may include a first monomer unit having an anionic functional group and a cationic functional group. In other words, an anionic functional group and a cationic functional group may exist in the first monomer unit.
[0069] Typically, the first monomer unit may have a phosphorylcholine group. The phosphorylcholine group is represented by -OP(=O)(-O - )OCH2CH2N + (-CH3)(-CH3)CH3 represents a moiety (-OP(=O)(-O - )O-) and the part that functions as a cationic functional group (-CH2CH2N + It is formed by (-CH3)(-CH3)CH3) bonds, therefore, it can be understood as an amphoteric functional group.
[0070] The amphoteric polymer may further include a second monomer unit having another anionic functional group in addition to the first monomer unit.
[0071] Alternatively, the amphoteric polymer may include a third monomer unit having an anionic functional group and a fourth monomer unit having a cationic functional group. In other words, the third monomer unit may have an anionic functional group but not a cationic functional group, and the fourth monomer unit may have a cationic functional group but not an anionic functional group.
[0072] In any case, the bonds between the monomer units constituting the amphoteric polymer are not particularly limited and may be any suitable bonds. For example, the amphoteric polymer may be an acrylic polymer. An acrylic polymer refers to a polymer containing a monomer unit derived from a (meth)acryloyl group as a main component. "(Meth)acryloyl" refers to an acryloyl group and / or a methacryloyl group. The main component refers to a component that accounts for more than 50% by mass of the polymer. The monomer unit derived from a (meth)acryloyl group may be, for example, represented by the formula: -CH2-C(-R 1 )(-COOR 2 )-(where R 1 is a hydrogen atom or a methyl group, R 2 It is an organic group having an anionic functional group and / or a cationic functional group, and may be a metal cation, a nonionic organic group, etc. depending on the situation).
[0073] As a commercially available resin material containing an amphoteric polymer, the Lipidure (registered trademark) series (manufactured by NOF Corporation) can be cited. For example, Lipidure (registered trademark)-HM contains a homopolymer of a first monomer unit having a phosphorylcholine group as a polymer component, and Lipidure (registered trademark)-A contains a copolymer of a first monomer unit having a phosphorylcholine group, a second monomer unit having a carboxylate group, and other nonionic monomer units as polymer components.
[0074] Commercially available resin materials may contain any appropriate additives in addition to the amphoteric polymer. Examples of additives include, but are not limited to, liquid media, surfactants, curing agents and / or crosslinking agents, and viscosity modifiers (eg, thickeners).
[0075] <Liquid Composition>
[0076] A liquid composition comprising the MXene particles and the amphoteric polymer prepared separately as above in a liquid medium is prepared.
[0077] The liquid medium can be any one of an aqueous medium and an organic medium, preferably an aqueous medium. The aqueous medium is representatively water, and depending on the circumstances, in addition to water, other liquid substances can also be included in a smaller amount (for example, 30% by mass or less, preferably 20% by mass or less, based on the entire aqueous medium). The organic medium is not particularly limited, and for example, can be a protic solvent or an aprotic solvent represented by an alcohol, or can be a mixed solvent of two or more thereof.
[0078] The obtained liquid composition can well disperse MXene particles in the liquid medium through the amphoteric polymer. As described later, by using a liquid composition with improved dispersibility of MXene particles, high strength and low impedance can be achieved in the final film.
[0079] The ratio of the amphiphilic polymer in the liquid composition to the total of the MXene particles and the amphiphilic polymer is 5% by volume or more and 70% by volume or less. Within this range, the effects of high strength and low impedance can be exerted. It is believed that the above ratio in the liquid composition is substantially the same as the ratio of the amphiphilic polymer 11 to the total of the MXene particles 10 and the amphiphilic polymer 11 in the final film 20.
[0080] The liquid composition may be in the form of a slurry or a paste, depending on the total solid content concentration of the MXene particles and the amphoteric polymer.
[0081] Process (b)
[0082] <Precursor film>
[0083] Next, a precursor film is formed on a substrate using the liquid composition prepared above, and at least the precursor film is dried to obtain a film (more specifically, a conductive film).
[0084] The substrate is not particularly limited, and can be composed of any appropriate material, and can have any appropriate structure and / or form. In the surface of the substrate, the area where the precursor film is formed can be flat or uneven, for example, it can have a surface shape such as a curved surface, a concave-convex shape, an indefinite shape, etc. The substrate can be representatively a substrate, a film, etc., but is not limited to these. The material of the substrate is not particularly limited. The substrate can be exemplified by a case where it is formed by a conductive material. As a conductive material, at least one material of gold, silver, copper, platinum, nickel, titanium, tin, iron, zinc, magnesium, aluminum, tungsten, molybdenum and a conductive polymer as a metal material can be cited. The substrate can have a conductive film such as a metal film different from the film of the present embodiment on the contact surface with the film (conductive film) of the present embodiment. Alternatively, the above-mentioned substrate can be formed by an organic material. As the above-mentioned organic material, for example, a flexible organic material can be cited, for example, a thermoplastic polyurethane elastomer (TPU), a PET film, a polyimide film, a liquid crystal polymer film, etc. can be cited.
[0085] In the case where high adhesion is required between the final film and the substrate, the substrate surface (the surface of the precursor film) preferably has a functional group (such as an OH group, etc.) that can hydrogen bond with the MXene particles. The functional group can be a functional group that the substrate originally has, or a functional group that is manifested by performing a pretreatment (such as a plasma treatment). The pretreatment can be performed for the purpose of cleaning, hydrophilization, etc.
[0086] However, the film of the present embodiment may be in the form of a self-standing film that is finally separated from the substrate. In this case, adhesion between the film and the substrate is not required.
[0087] The method for forming a precursor film on a substrate is not particularly limited, for example, a precursor film can be formed by spraying a liquid composition on a substrate. However, it is also possible to form a precursor film on a porous member by a method other than spraying, such as using a porous member (such as a membrane filter) as a substrate, so that the liquid composition passes through the porous member (filtering), thereby forming a precursor film on the porous member. Spraying can orient MXene particles on a substrate (arranged in a manner that the two-dimensional sheet plane of MXene particles is roughly parallel to the surface of the substrate (for example, within ± 20 °)), and can make the final film denser than a filter membrane, so that higher environmental resistance (moisture resistance) can be obtained. In addition, any method such as rod coating, spin coating, and dipping can also be applied.
[0088] When the precursor film is dried, unnecessary liquid medium is removed (not all of the liquid medium is necessarily removed, and a part of the liquid medium may remain), and a film is formed. In order to obtain a film of a desired thickness, the above-mentioned spraying and drying may be repeated.
[0089] <Film>
[0090] The film obtained as described above is made using a liquid composition in which the dispersibility of MXene particles is improved by an amphoteric polymer, so that high strength and low impedance can be achieved at the same time. Since the film of this embodiment has high strength, a self-supporting film can be easily obtained by removing the substrate when desired.
[0091] The present invention is not limited by any theory, and the reason why the amphoteric polymer can provide a liquid composition with good dispersibility of MXene particles, improve the strength of the film finally obtained, and reduce the impedance is considered to be as follows.
[0092] MXene particles are made of m X n The surface of the layer body shown has a modification or terminal T (T is selected from at least one of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom), and there is a charged site by this composition. The two-dimensional sheet plane (a plane parallel to the layer of the MXene particle) that occupies most of the surface of the MXene particle is usually negatively charged. If the MXene particles are mixed with a liquid medium (representatively water), the MXene particles can be dispersed in the liquid medium by the repulsion of the negative charge, and some of them can be attracted to each other by intermolecular forces and hydrogen bonding forces and condensed. Therefore, the strength of the film made by mixing the MXene particles alone in the liquid medium is reduced. In order to uniformly mix the MXene particles and the polymer in the liquid medium, it is considered to use a polymer with high affinity for the MXene particles and polarity, rather than a polymer with poor polarity. However, for example, although polyurethane (refer to patent document 1) has high polarity, for the liquid composition in which MXene particles and polyurethane are mixed in the liquid medium, MXene particles may condense, and it is difficult to obtain a high-strength and low-impedance film.
[0093] In the present embodiment, in addition to MXene particles and liquid medium, amphoteric polymers (polymers having anionic functional groups and cationic functional groups) are used in a specified ratio. By using amphoteric polymers, the dispersion mechanism based on electrostatic repulsion is well demonstrated, and MXene particles and amphoteric polymers can be mutually miscible in a liquid medium and maintain a good dispersion state. In more detail, it can be considered that the cationic functional groups of the amphoteric polymer partially adsorb negatively charged MXene particles, and the anionic functional groups of the amphoteric polymer partially repel each other electrostatically, and the adsorption and electrostatic repulsion are appropriately balanced, and the steric hindrance of the amphoteric polymer effectively prevents the MXene particles from agglomerating with each other, so that the MXene particles can be well dispersed. In a film made using a liquid composition in which MXene particles and amphoteric polymers are mixed in a liquid medium at a specified ratio, MXene particles are well dispersed relative to the amphoteric polymer, so that high strength and low impedance can be taken into account.
[0094] In the finally obtained film 20, the ratio of the amphoteric polymer 11 to the total of the MXene particles 10 and the amphoteric polymer 11 is 5 volume % or more and 70 volume % or less, similar to the ratio in the liquid composition used. Within this range, the effects of high strength and low impedance can be exerted.
[0095] The strength of the film can be determined, for example, by the presence or absence of cohesive failure. The film formed of the MXene monomer material simply undergoes cohesive peeling during tape peeling (according to the cross-hatch method specified in JIS K5600-5-6:1999). In contrast, the film of the present embodiment contains MXene particles and amphoteric polymers in a specified ratio, so cohesive peeling can be prevented, resulting in high film strength.
[0096] Regarding impedance, if the impedance of a film composed of a composite material of MXene particles and a polymer is equal to or lower than that of a film composed of a single MXene material (e.g., Reference Example 1 described later), it can be judged as low impedance. According to the measurement conditions shown in the examples described later, for example, at 10 Hz, it is preferably 340 Ohm or less, and more preferably 330 Ohm or less.
[0097] The ratio of anionic functional groups to cationic functional groups in the amphoteric polymer 11 is not particularly limited. In some examples, the amphoteric polymer 11 is not too cationic as a whole, and is preferably neutral or anionic. In some examples, the amphoteric polymer 11 is preferably hydrophilic as a whole.
[0098] The film 20 of the present embodiment is a conductive film and can be used for any appropriate application, for example, for applications requiring conductivity, such as electrodes in any appropriate electrical devices and electromagnetic shields (EMI shields).
[0099] The electrode is not particularly limited, and may be, for example, a biosignal sensing electrode, a capacitor electrode, a battery electrode, a sensor electrode, an antenna electrode, an electrical stimulation electrode, etc. By using the membrane of this embodiment, a low-impedance and high-sensitivity biosignal sensing electrode, a large-capacity capacitor and battery, a high-sensitivity sensor and antenna can be obtained even with a smaller volume (device occupied volume).
[0100] The biosignal sensing electrode is an electrode for sensing (obtaining) a biosignal. The biosignal sensing electrode may be, for example, an electrode for measuring EEG (electroencephalogram), ECG (electrocardiogram), EMG (electromyogram), or EIT (electrical impedance tomography), but is not limited thereto.
[0101] The capacitor may be an electrochemical capacitor. An electrochemical capacitor is a capacitor that utilizes the capacity resulting from the physical and chemical reaction between an electrode (electrode active material) and ions (electrolyte ions) in an electrolyte, and can be used as a device for storing electrical energy (electricity storage device). A battery may be a chemical battery that can be repeatedly charged and discharged. For example, the battery may be a lithium ion battery, a magnesium ion battery, a lithium sulfur battery, a sodium ion battery, etc., but is not limited thereto.
[0102] Sensor electrodes are electrodes used to detect target substances, states, abnormalities, etc. Sensors may be, for example, gas sensors, biosensors (chemical sensors that utilize molecular recognition mechanisms of biological origin), etc., but are not limited to these. Antenna electrodes are electrodes used to radiate electromagnetic waves into space and / or receive electromagnetic waves in space.
[0103] The electrical stimulation electrode is an electrode for applying electrical stimulation to a living body. The electrical stimulation can be applied to a living body, particularly to a living body tissue such as the spinal cord, brain, nerve tissue, muscle tissue, etc., but is not limited thereto.
[0104] By using the film of this embodiment, an electromagnetic shielding body having a high shielding ratio (EMI shielding property) can be obtained.
[0105] Although the film in one embodiment of the present invention has been described in detail above, the present invention can be modified in various ways. It should be noted that the film of the present invention can also be produced by a method different from the production method in the above embodiment.
[0106] Example
[0107] (Example 1)
[0108] 1. Preparation of Layered Material Particles
[0109] The following steps were successively carried out: (1) preparation of the precursor (MAX), (2) etching of the precursor, (3) cleaning after etching, (4) intercalation of Li, and (5) delamination, thus obtaining MXene particles for the first time.
[0110] (1) Preparation of the precursor (MAX)
[0111] TiC powder, Ti powder, and Al powder (all manufactured by High Purity Chemical Research Institute Co., Ltd.) were put into a ball mill containing zirconia balls in a molar ratio of 2:1:1 and mixed for 24 hours. The obtained mixed powder was sintered at 1350 °C for 2 hours under an Ar atmosphere. The obtained sintered body (block-shaped MAX) was crushed with a vertical milling cutter to a maximum size of 40 μm or less. Thus, Ti3AlC2 particles as the precursor (powder-shaped MAX) were obtained.
[0112] (2) Etching of the precursor (MAX)
[0113] Using the Ti3AlC2 particles (powder) prepared by the above method, etching was carried out under the following etching conditions to obtain a solid-liquid mixture (slurry) containing the solid components from the Ti3AlC2 powder.
[0114] (Etching conditions)
[0115] · Precursor: Ti3AlC2 (screened through a 45 μm sieve)
[0116] · Etching solution composition: 6 mL of 49% HF
[0117] 18 mL of H2O
[0118] 36 mL of HCl (12 M)
[0119] · Precursor input amount: 3.0 g
[0120] · Etching container: 100 mL IBOY (Japanese: ァイボ一イ)
[0121] · Etching temperature: 35 °C
[0122] · Etching time: 24 h
[0123] · Stirrer rotation speed: 400 rpm
[0124] (3) Cleaning after etching
[0125] The slurry was equally divided into two parts and inserted into two 50 mL centrifuge tubes respectively. Then, after centrifugation at 3500G for 5 minutes using a centrifuge, the supernatant was discarded. Then, (i) 35 mL of pure water was added to the remaining precipitate in each centrifuge tube, (ii) it was stirred by hand shaking, (iii) it was centrifuged at 3500G for 5 minutes, and (iv) the supernatant was removed. The steps (i) to (iv) were repeated 10 times. Finally, Ti3C2T was obtained by centrifugation at 3500G for 5 minutes. s -Moisture medium clay.
[0126] (4) Li intercalation
[0127] For Ti3C2T prepared by the above method s - Moisture medium clay, according to the following Li intercalation conditions, using LiCl as a Li-containing compound, stirring at 20° C. to 25° C. for 12 hours, to perform Li intercalation. The detailed conditions of Li intercalation are as follows.
[0128] (Li intercalation conditions)
[0129] Ti3C2T s - Moisture medium clay (MXene after washing): solid content 0.75g
[0130] LiC1: 0.75g
[0131] Intercalation container: 100mL IBOY
[0132] Temperature: 20°C or above and 25°C or below (room temperature)
[0133] Time: 12h
[0134] Stirrer speed: 800rpm
[0135] (5) Delamination and water washing
[0136] The slurry obtained by Li intercalation is put into a 50mL centrifuge tube, centrifuged at 3500G using a centrifuge, and the supernatant is discarded. Next, (i) 40mL of pure water is added to the remaining precipitate, stirred with an oscillator for 15 minutes, (ii) centrifuged at 3500G, and (iii) the supernatant is recovered as a liquid containing monolayer and few-layer MXene. The operations (i) to (iii) are repeated a total of 4 times to obtain a supernatant containing monolayer and few-layer MXene. Furthermore, the supernatant is centrifuged at 4300G and 2 hours using a centrifuge, and the supernatant is discarded, and MXene clay containing monolayer and few-layer MXene is obtained as the remaining precipitate.
[0137] 2A. Preparation of MXene Monomer Material Slurry (Reference Example 1)
[0138] A predetermined amount of 50 mL of the MXene clay obtained in 1 above was taken into a centrifuge tube, and pure water was added. At this time, the amount of pure water added was adjusted so that the concentration of MXene in the mixture became 1.5% by mass. Then, the mixture was stirred with an oscillator for 15 minutes to obtain a MXene slurry as a liquid composition.
[0139] 2B. Preparation of MXene / polymer composite material slurry (Examples 1 to 5 and Comparative Examples 1 to 4)
[0140] A predetermined amount of 50 mL of the MXene clay obtained in 1 above was taken into a centrifuge tube, and then, for Examples 1 to 5 and Comparative Examples 1 to 4, any one of the polymer dispersions P1 to P3 and polymers P4 to P5 in Table 1 was added according to the "Polymer / Polymer Dispersion" column in Table 2, and pure water was added appropriately. At this time, the addition amount of P1 to P5 and pure water was adjusted so that the concentration of MXene in the mixture became 1.5% by mass, and the ratio of the polymer in the dry film to the total of MXene (MXene particles) and polymer became the value of the "Polymer Ratio" shown in Table 2. Then, the mixture was stirred with an oscillator for 15 minutes to obtain a slurry of a MXene / polymer composite material as a liquid composition.
[0141]
Table 1
[0142]
[0143]
Table 2
[0144]
[0145] In Table 2, the symbol "-" indicates that no evaluation could be performed because a self-supporting film could not be produced.
[0146] 3. Preparation of membrane samples
[0147] Using each of the slurries obtained in 2A and 2B above, the following procedures were carried out to prepare film samples.
[0148] (a) Add the slurry into a 25 mL syringe.
[0149] (b) The syringe of (a) above is installed in a sprayer.
[0150] (c) The polyimide substrate is placed on a stage with suction of a spray coater.
[0151] (d) The atomization pressure was set to 0.5 MPa, the distance between the nozzle tip and the substrate was set to 15 cm, the liquid delivery rate was set to 5 mL / s, the scanning speed was set to 150 mm / s, and the stage heater was set to 45°C.
[0152] (e) The substrate was coated 15 times to form a precursor film.
[0153] (f) Drying was performed in a normal pressure oven at 80° C. for 2 hours and in a vacuum oven at 150° C. for 16 hours to obtain a film (dried film) sample.
[0154] 4. Sample evaluation
[0155] (1) Impedance
[0156] The impedance was measured as follows.
[0157] (a) A self-supporting film was obtained by removing the polyimide substrate from the film sample prepared on the polyimide substrate in 3 above, using the self-supporting film as a working electrode, using a platinum electrode as a counter electrode, and using a silver-silver chloride electrode as a reference electrode to assemble a beaker cell. The working electrode was set to have a diameter of 1.5 mm, and the counter electrode was set to have a size larger than that of the working electrode.
[0158] (b) As the measurement conditions, the frequency is 0.1 Hz to 10 5 Hz, the voltage was set to 10 mVrms relative to the open circuit voltage, the number of plotted points in the entire measurement frequency region was set to 61 points, and the number of N per plotted point was set to 1 to 10, and the measurement was performed in a constant potential mode. The device used was a VMP-300 high-performance electrochemical measurement system (16ch·Advanced Mode 1) from Bio-Logic Science Instruments. As the measurement results, the impedance at 10 Hz is shown in Table 2.
[0159] (2) Strength (tape peel test)
[0160] The strength (bonding strength) of the film samples prepared on the polyimide substrate in the above 3 was evaluated by the cross-cut method specified in JIS K5600-5-6: 1999. The evaluation results were classified as follows.
[0161] 0: The cut edges are completely smooth and there is no peeling of the grid at any point.
[0162] 1: There is slight peeling of the coating film at the intersection of the cuts. The affected portion of the cross-cut portion is definitely not more than 5%.
[0163] 2: The coating film peels off along the cut edges and / or at the intersections. The affected portion in the cross-cut portion is definitely more than 5%, but not more than 15%.
[0164] 3: The coating peels off locally or entirely along the cut edge, and / or individual parts of the mesh peel off locally or entirely. The affected area of the cross-cut area is clearly more than 15%, but not more than 35%.
[0165] 4: The coating peels off locally or entirely along the cut edge, and / or the cross-section peels off locally or entirely at several locations. The affected area of the cross-section does not exceed 65%.
[0166] 5: Any degree of peeling that cannot be classified in category 4.
[0167] (3) Distance between layers (d 002 )
[0168] The interlayer distance (d 002 ) determination.
[0169] (a) The film sample prepared on the polyimide substrate in the above 3 was cut into 2 cm squares and measured by XRD (characteristic X-ray: CuKα) using an X-ray diffractometer (manufactured by Rigaku Co., Ltd., SmartLab3 and SmartLab Studio II software) ), and obtained the XRD curve of the θ-axis scanning in the range of 2θ=2 degrees to 50 degrees. The step size was set to 0.02 degrees, and the scanning speed was set to 5 degrees / minute.
[0170] (b) At around 2θ = 7 degrees, the MXene (Ti3C2T s ), so the θ, n = 1, (CuKα ray wavelength) is applied to the Bragg formula (2dsinθ=nλ) to find the interplanar spacing d of the (002) plane. 002 The value was taken as the interlayer distance. The results are shown in Table 2.
[0171] Referring to Table 2, in Examples 1 to 5 involving film samples in which amphoteric polymers and MXene particles are mixed at a polymer ratio of 5 to 70% by volume, lower impedance than Reference Example 1 involving a film sample containing only MXene particles (without polymer) is obtained, and high film strength is shown. On the other hand, in Comparative Example 1 involving a film sample in which amphoteric polymers and MXene particles are mixed at a polymer ratio of 75% by volume, although the film strength is high, the impedance is significantly higher than Reference Example 1. It can be understood that the higher the polymer ratio in the film, the greater the interlayer distance d of the MXene. 002 It is believed that if the polymer ratio in the film exceeds 70% by volume, for example, 75% by volume, the interlayer distance d of MXene will be 002 When the value exceeds a certain threshold, the conductivity of the film is significantly reduced, and the impedance becomes too high. Compared with Examples 1 to 5 and Comparative Example 1 using amphoteric polymers, in Comparative Example 2 using an ionomer of polyethylene-methacrylic acid copolymer, Comparative Example 3 using hydrophobic paraffin, and Comparative Example 4 using cationic PVOH without anionic functional groups, the dispersibility of MXene particles and polymers in the slurry is poor, and the MXene particles and polymers in the obtained film (dried film) cannot be well miscible (separated), the strength is low (simple coagulation and peeling), and a self-supporting film cannot be obtained.
[0172] Industrial Applicability
[0173] The membrane of the present invention can be used for any appropriate purpose, and can be preferably used as, for example, an electrode, particularly a biosignal sensing electrode.
[0174] <1>
[0175] A film comprising particles of a two-dimensional material and a polymer, wherein the particles of the two-dimensional material comprise one or more layers,
[0176] The above layers include:
[0177] By the following formula: M m X n represents the layer body and the modification or terminal T present on the surface of the layer body,
[0178] (wherein, M is at least one metal of Group 3, 4, 5, 6, or 7,
[0179] X is a carbon atom, a nitrogen atom or a combination thereof,
[0180] n is greater than or equal to 1 and less than or equal to 4,
[0181] m is greater than n and less than 5),
[0182] (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom),
[0183] The polymer has anionic functional groups and cationic functional groups.
[0184] The ratio of the polymer in the film to the total of the particles of the two-dimensional material and the polymer is 5 volume % or more and 70 volume % or less.
[0185] <2>
[0186] according to <1> The membrane described in , wherein the polymer comprises a first monomer unit having the anionic functional group and the cationic functional group.
[0187] <3>
[0188] according to <2> The membrane described in , wherein the first monomer unit has a phosphorylcholine group.
[0189] <4>
[0190] according to <2> or <3> The membrane described in , wherein the polymer further comprises a second monomer unit having another anionic functional group.
[0191] <5>
[0192] according to <1> ~ <4> The membrane described in any one of the above, wherein the polymer comprises a third monomer unit having the anionic functional group and a fourth monomer unit having the cationic functional group.
[0193] <6>
[0194] An electrode comprising <1> ~ <5> The film according to any one of the above.
[0195] <7>
[0196] according to <6> The electrode recorded in is a biological signal sensing electrode.
[0197] <8>
[0198] according to <6> The electrode described in is an electrical stimulation electrode.
[0199] Description of Reference Numerals
[0200] 1a, 1b: Layer body (M m X n layer)
[0201] 3a, 5a, 3b, 5b: modified or terminal T
[0202] 7a, 7b: MXene layer
[0203] 10, 10a, 10b: MXene particles (particles of two-dimensional materials)
[0204] 11: Amphoteric polymer (polymer with anionic and cationic functional groups)
[0205] 20: Membrane
Claims
1. A film comprising particles of a two-dimensional material and a polymer, wherein the particles of the two-dimensional material comprise one or more layers, The layer comprises the following formula: M m X n represents the layer body and the modification or terminal T present on the surface of the layer body, Formula M m X n wherein M is at least one metal of Group 3, 4, 5, 6 or 7, X is a carbon atom, a nitrogen atom or a combination thereof, n is greater than or equal to 1 and less than or equal to 4, m is greater than n and less than 5, T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom, The polymer has anionic functional groups and cationic functional groups, The ratio of the polymer in the film to the total of the particles of the two-dimensional material and the polymer is 5 volume % or more and 70 volume % or less.
2. The film according to claim 1, wherein The polymer includes a first monomer unit having the anionic functional group and the cationic functional group.
3. The film according to claim 2, wherein The first monomer unit has a phosphorylcholine group.
4. The film according to claim 2 or 3, wherein The polymer further includes a second monomer unit having another anionic functional group.
5. The film according to any one of claims 1 to 4, wherein The polymer includes a third monomer unit having the anionic functional group and a fourth monomer unit having the cationic functional group. 6 . An electrode comprising the film according to claim 1 . The electrode according to claim 6 , which is a biological signal sensing electrode. The electrode according to claim 6 , which is an electrical stimulation electrode.
